Optimized output electricity of thermoelectric generators by matching phase change material and thermoelectric material for intermittent heat sources. (15th October 2021) - Tian, Yuanyuan; Liu, Anbang; Wang, Junli; Zhou, Yajie; Bao, Chengpeng; Xie, Huaqing; Wu, Zihua; Wang, Yuanyuan
Abstract: Thermoelectric generators (TEGs) are usually working in intermittent heat source environments, and thus the phase change material (PCM) has been widely adopted in to maintain relatively stable temperature difference. The property matching between the PCM and the TEGs is one of the crucial problems to influence the performance of the PCM-TEG system. In this work, the influence of the phase change temperature of the PCM on the output power and generated electricity of PCM-TEG system is studied. Classic Enthalpy model and three-dimensional coupled thermo-electric equations are applied to study the heat transfer and energy conversion mechanisms. Our results show that the output electric energy of a PCM-TEG system can be optimized by tuning the phase change temperature of PCM. The total generated electricity can be enhanced as large as 15.6% by matching the PCM with the thermoelectric properties of the thermoelement. Moreover, by comparing three cases with different thermoelectric materials, we give relationship between the optimal phase change temperature of PCM and the temperature for maximum figure of merit (ZT) of the thermoelement, which provides a selection criterion of PCM for TEG module. Our work could be helpful to realize further high efficiency thermoelectric generators for intermittent heat sources. Highlights: Phase change material-thermoelectric generator system proposed for intermittent heat source. Phase change temperature is optimized to maximize total generated electricity. Optimal phase change temperature is determined by the thermoelements. A selection criterion of optimal phase change material is addressed.